CD74 is dispensable for development of chronic lymphocytic leukemia in Eµ-TCL1 transgenic mice. Issue 12 (14th October 2020) - Barthel, Romy; Fedorchenko, Oleg; Velmans, Tanja; Rosen, Natascha; Nguyen, Phuong-Hien; Reinart, Nina; Florin, Alexandra; Herling, Marco; Hallek, Michael; Fingerle-Rowson, Günter
Abstract: CD74 is a surface protein expressed on immune cells, which acts as receptor for the chemokine macrophage migration inhibitory factor (MIF). Signaling via the MIF/CD74-axis has been reported to be important for the pathogenesis of chronic lymphocytic leukemia (CLL). We wanted to clarify the role of CD74 in MIF-induced signaling/leukemic development. In Eμ-TCL1 transgenic mice, occurrence of the leukemic phenotype was associated with increased surface CD74 expression. Eμ-TCL1 +/+ Cd74 −/− mice showed similar kinetics and clinical features of CLL development as Eμ-TCL1 +/+ mice. MIF stimulation of leukemic splenocytes led to AKT activation in a CD74-dependent manner. AKT activation was reduced in Cd74-deficient splenocytes in the presence of the oncogenic TCL1-transgene. Tumor cell apoptosis/proliferation were unaffected in Eμ-TCL1 +/+ Cd74 −/− mice. Our data suggest that the need for active CD74 signaling is overcome in the leukemic context of TCL1-driven CLL, and that CD74 may have a dispensable role for CLL pathogenesis in this model.